Communication skills of children from Roma families in Slovak language in the first year of primary schools - Vanková, Katarína; Rosinský, Rastislav; Čerešníková, Miroslava (International Journal of Psychosocial Rehabilitation, 2019)
The need for man to communicate, socialize, form and develop social relationships with other people is one of the basic existential needs of the human race. This need is realized in the context of social relations.In every person's life, the first language is the mother tongue, by which social communication takes place first in the family, then in kindergartens and primary schools.The developed mother tongue is an advantage of a child when starting school. The mother tongue is the language children learn as the first one in the process of socialization (Lemhöfer, K., Schriefers, H., &Hanique, I. 2010), the language children have learnt in their life, and which influences their future. Also Basil Bernstein (1971) considers a language the main means of person’s socialization, and emphasizes a direct relationship between a social group and a language.In our paper, we discuss language competence in pupils in the first year of school attendance.Our main goal is to compare the language competence of pupils from Roma families whose mother tongue is Roma with pupils whose mother tongue is Slovak. Both groups attend elementary schools with Slovak language.The sample included pupils with the Romani mother tongue (n1=69) and pupils with the Slovak mother tongue (n2=76); the pupils attended the first year of primary schools with the Slovak language of instruction. The field diagnosis had two phases: the initial phase – at the beginning of a school year in September, and the final phase – at the end of the school year in June. In our study, we used the Heidelberg Speech Development Test (H-S-E-T, Grimmová, Schöller, Mikulajová, 1997), where the authors differentiate between language competence, language performance, and language levels. The test provides a rather complex picture about an achieved level of language development in children of younger school age. Our testing within the Heidelberg test focused on Sentence building (SB). The findings that we state are interesting also in the moment where the diagnosed children whose mother tongue is Romani had significantly lower scores than the children whose mother tongue is Slovak in comparison of the studied period September - June. We associate this status with the possibility that children whose mother tongue is Romani come from socially disadvantaged environment that is accompanied by poverty and social exclusion.(Vanková, K., 2017) The environment children grow up in significantly influences their communication abilities. To some extent, our findings correspond with Pierre Bourdieu (1990) who, based on his theory, states that children from socially more stimulating environment – families gain better habitus and cultural capital because they are  more prepared for school, are more linguistically capable, and understand the notions significantly better, and vice versa. We emphasize the fact that performance of children from Roma families with the Romani mother tongue is average, and we evaluate the differences in the scoring as statistically significant. The found differences are significantly lower and the progress in vocabulary is not very significant in the studied period in the children with the Romani mother tongue in comparison with the children with the Slovak mother tongue.